HUBUNGAN SELF-MANAGEMENT DENGAN KUALITAS HIDUP PASIEN HIPERTENSI DI UPT PUSKESMAS GARUDA KOTA BANDUNG TAHUN 2025 - Karmila, Mila; Kusmiran, Eny; Purwanti, Tentry Fuji (MAJU : Indonesian Journal of Community Empowerment, 2025)
Background: Hypertension is a non-communicable disease whose prevalence continues to increase globally and is a major risk factor for various cardiovascular complications. Self-management is an important aspect of hypertension control, as successful therapy depends not only on medical treatment, but also on the patient's active role in managing lifestyle, adherence to therapy, and regular blood pressure monitoring. However, many hypertensive patients experience difficulties in implementing effective self-management, which may result in a decrease in their quality of life. Objective of the study: Analyzing the relationship between self-management and the quality of life of hypertensive patients. Methods: This type of research is a quantitative research using a Cross sectional design. The sample used in this research was 68 respondents, with the data collection technique used was accidental sampling. The questionnaire used was in the form of the Hypertension Self Management Behavior Quetionnair (HSMBQ) and WHOQOL-BREF questionnaires with the data analysis used being a bivariate analysis, namely the Chi-Square test. Results: based on the results of the study, it was found that the majority of self-managemet respondents in the poor category were 28 people (41.2%). the majority of respondents' quality of life in the poor category were 25 respondents (36.8). based on the results of testing with the Chi-Square test, it was found that there was a relationship between self-managemet and quality of life, the p value = <0.001 <0.05.